Effect of Statins on Renal Function and Total Kidney Volume in Autosomal Dominant Polycystic Kidney Disease - Cheng Xue; Li-Ming Zhang; Chenchen Zhou; Chang-Lin Mei; Sheng-Qiang Yu (Karger Publishers, 2020)
Background: Autosomal dominant polycystic kidney disease (ADPKD) is the most common hereditary nephropathy with few treatments to slow renal progression. The evidence on the effect of lipid-lowering agents (statins) on ADPKD progression remains inconclusive. Methods: We performed a systematic review and meta-analysis by searching the PubMed, Embase, Web of Science, and Cochrane databases (up to November 2019). Changes in estimated glomerular filtration rate (eGFR) and total kidney volume (TKV) were the primary outcomes. Mean differences (MDs) for continuous outcomes and 95% confidence intervals (CIs) were calculated by a random-effects model. Results: Five clinical studies with 648 participants were included. Statins did not show significant benefits in the yearly change in eGFR (4 studies, MD = −0.13 mL/min/m2, 95% CI: −0.78 to 0.52, p = 0.70) and the yearly change in TKV (3 studies, MD = −1.17%, 95% CI: −3.40 to 1.05, p = 0.30) compared with the control group. However, statins signiﬁcantly decreased urinary protein excretion (−0.10 g/day, 95% CI: −0.16 to -0.03, p = 0.004) and serum low-density lipoprotein level (−0.34 mmol/L, 95% CI: −0.58 to −0.10, p = 0.006). Conclusion: Despite these proteinuria and lipid-lowering benefits, the effect of statins on ADPKD progression was uncertain.